2007
DOI: 10.1002/hbm.20388
|View full text |Cite
|
Sign up to set email alerts
|

Relation between muscle and brain activity during isometric contractions of the first dorsal interosseus muscle

Abstract: We studied the relationship between muscle activity (electromyography, EMG), force, and brain activity during isometric contractions of the index finger, on a group and individual level. Ten subjects contracted their right or left index finger at 5, 15, 30, 50, and 70% of their maximal force. Subjects received visual feedback of the produced force. We focused our analysis on brain activation that correlated with EMG. Brain activity of specific anatomical areas (region-of-interest analysis, ROI) was quantified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
63
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 51 publications
18
63
1
Order By: Relevance
“…Our contrast analysis revealed that during sustained contractions a large motor network is activated, including the SMC, supplementary motor area (SMA), cingulate motor area (CMA), premotor areas and cerebellum [See also Table I; Dettmers et al, 1995;Thickbroom et al, 1998;van Duinen et al, 2008]. The comparison between the activation during the last (T3) and first (T1) third of the sustained high-force contraction showed increased activation in clusters in the precentral gyrus, SMA, CMA, and the parietal operculum.…”
Section: Brain Areas and Roi Analysismentioning
confidence: 89%
“…Our contrast analysis revealed that during sustained contractions a large motor network is activated, including the SMC, supplementary motor area (SMA), cingulate motor area (CMA), premotor areas and cerebellum [See also Table I; Dettmers et al, 1995;Thickbroom et al, 1998;van Duinen et al, 2008]. The comparison between the activation during the last (T3) and first (T1) third of the sustained high-force contraction showed increased activation in clusters in the precentral gyrus, SMA, CMA, and the parietal operculum.…”
Section: Brain Areas and Roi Analysismentioning
confidence: 89%
“…Although we correctly hypothesised an increase in contralateral synergist muscle strength, we thought (incorrectly) this would be accompanied by increased corticomotor excitability projecting to the untrained synergist wrist flexors. This hypothesis was based on well-established evidence, that unilateral voluntary contractions not only activate the contralateral motor pathway, but also the ipsilateral motor pathway targeting the resting or untrained limb Hortobágyi et al 2003;Ruddy et al 2017;van Duinen et al 2008;Perez and Cohen 2008;Verstynen and Ivry 2011;Carson and Ruddy 2013;Hendy and Kidgell 2014;Zult et al 2016). On this basis, it was likely that the untrained synergist wrist flexors would experience increased excitability following training, because of its isometric role in the strength training protocol and because of the contribution of shared corticospinal inputs between agonists and synergists (Smith and Fetz 2009;Capaday et al 2013).…”
Section: Corticomotor Excitability Is Spatially Confined To the Untramentioning
confidence: 99%
“…Achieving adequate levels of force may be considered a secondary requirement. Recent evidence identifying a cortical network in frontal and parietal areas linked to motor output of the index finger that is independent of the level of EMG (van Duinen et al, 2008) supports the possibility that cortical areas for muscle force are dissociable from other features of motor control.…”
Section: Introductionmentioning
confidence: 95%